Psychiatric Morbidity Profiles of Child & Adolescent Patients in General Psychiatry Clinic - Rastogi, Pali; Rastogi, Deepti (International Journal of Innovative Research in Medical Science, 2018)
Introduction: There are limited data on child mental health needs. Therefore study to determine the prevalence rates of child and adolescent disorders was undertaken. Methods: Retrospective file review study was conducted in general psychiatry clinic including the patients under 18 years of age. Diagnosis was noted as per ICD 10 criteria. Results: Majority who took consultation were males (63.63%) of urban background (61.82%) belonging to Hindu religion (90.90%). Most of the patients were between 13-18 years age group (61.82%) with prevalence of mental retardation 23.63%, neurotic and stress related disorders (14.55%), affective disorders (12.73%), emotional and behavioral disorders (11.82%), psychosis (11.82%) and epilepsy (12.73%) respectively. Conclusion: Data from general psychiatry clinic is helpful to define needs and priorties of child and adolescent age group.